A single-tube nested PCR for Pneumocystis carinii f. sp. hominis. - Tang, X (1997)
A single-tube nested PCR which amplifies the internal transcribed spacer (ITS) regions of the rRNA genes of human Pneumocystis carinii was developed. The outer primers for the first PCR, which anneal to the 18S and the 26S rRNA genes of P. carinii, were made to have a midpoint temperature (Tm) of 74 degrees C. The inner primers for the second PCR have a Tm of 56 to 58 degrees C and are specific for human P. carinii; they anneal to an area close to the beginning of ITS1 and the junction of ITS2 and the 26S rRNA genes. The reaction mixture contained 2.5 pmol of the first-PCR primers and 25 pmol of the second-PCR primers. The first PCR was performed at an annealing temperature of 68 degrees C, which did not allow the second-PCR primers to function. Since very small amounts (2.5 pmol) of the first-PCR primers were used, they were exhausted when the first PCR was completed. The single-tube nested PCR did not amplify P. carinii isolated from rats, mice, or ferrets. All 10 bronchoalveolar lavage (BAL) specimens from patients with P. carinii pneumonia were positive, whereas all 10 BAL specimens from patients with other diseases or patients infected with several commonly found fungi were negative by PCR.